(untitled) (Global Journal of Human-Social Science, 2019)
Unilateral intervention in the internal conflicts of other states all over the world has been part of superpower relations since the dawn of the modern nation-state in 1648. States that carry out such incursions usually premise their involvements on the need to maintain international peace and security on the one hand, and for humanitarian consideration at the other extreme. Since the end of the Second World War in 1945, America has intervened in various internal conflicts of other states all over the world. The usual justification has always been the need to either preserve peace within the international political system or to provide ’humanitarian assistance.’ Rather than use multilateral mechanisms in such engagements, the United States has always preferred unilateral intervention. It is within this context that America’s role in Syria is analyzed. The emphasis of this work shows the impact of American unilateralism in Syria, the Middle East and the world at large.